2010
DOI: 10.1589/rika.25.779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Care Prevention Course on Health-Related QOL and Motor Function According to History of Falls

Abstract: [Purpose] We conducted a care prevention course for potentially dependent elderly and investigated its effect on their health-related QOL and motor function.[Subjects] The subjects were 45 potentially dependent elderly persons (11 men, 34 women) who enrolled for the care prevention course.[Methods] The care prevention course lasted 3 months and was conducted once a week for 12 weeks. Each session lasted 2 hours and consisted of a lecture, stretching, muscle strength training and whole body exercise. The asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Itoh et al1 ) compared individuals with and without fall history experiences after exercise intervention, and reported that no improvement in the QOL was observed in the former, while the motor function improved in both groups. Based on this finding, falls may be a negative factor for the elderly's independence, decreasing their QOL, in addition to their physical functions.…”
Section: Introductionmentioning
confidence: 99%
“…Itoh et al1 ) compared individuals with and without fall history experiences after exercise intervention, and reported that no improvement in the QOL was observed in the former, while the motor function improved in both groups. Based on this finding, falls may be a negative factor for the elderly's independence, decreasing their QOL, in addition to their physical functions.…”
Section: Introductionmentioning
confidence: 99%